1996
DOI: 10.1093/gerona/51a.6.m297
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Changes in Gait Speed in Older Adults

Abstract: The results suggest, in the range of fitness of the study sample, that changes in gait speed are related to changes in depressive symptoms and physical health status, but not to modest changes in fitness. A model assuming nonlinear relationships may be appropriate for understanding how strength and aerobic capacity affect gait speed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
80
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 16 publications
9
80
2
2
Order By: Relevance
“…An abundance of research evidence has demonstrated that OA walk differently than younger adults (YA) (Prince et ai, 1997;Judge, Ounpuu, & Davis, 1996;Buchner et al, 1996;Alexander, 1994;Nutt, Marsden, & Thompson, 1993). For example, Winter (1991) reported that OA walked with wider strides and shorter steps compared to younger adults (YA).…”
Section: Age Related Changes In the Kinematics Of Gaitmentioning
confidence: 99%
“…An abundance of research evidence has demonstrated that OA walk differently than younger adults (YA) (Prince et ai, 1997;Judge, Ounpuu, & Davis, 1996;Buchner et al, 1996;Alexander, 1994;Nutt, Marsden, & Thompson, 1993). For example, Winter (1991) reported that OA walked with wider strides and shorter steps compared to younger adults (YA).…”
Section: Age Related Changes In the Kinematics Of Gaitmentioning
confidence: 99%
“…53 Whereas a nearly linear relationship accounted for gains in muscle strength and improved function for the frail elderly, a nonlinear relationship accounted for the smaller gains following a similar intervention in a well-elder population. 54 In our investigation, for example, the strength of the association between lower extremity strength and gait speed suggests that the patients are frail. The distribution and mean values of performance measures also support the contention that the participants are frail.…”
Section: Discussionmentioning
confidence: 61%
“…[23][24][25][26] Twenty-one to 44% of the variance in gait speed has been explained by a combination of height, calf strength, activity level, pain, health status, weight, maximal oxygen consumption, and lower extremity strength scores. [25][26][27][28] Similarly, 25 to 40% of the variance in maximal gait speed has been explained by quadriceps strength and one-legged balance. 23,28 Although the results suggest that lower extremity muscular performance is related to walking speed in elders, it is clear that a large portion of the variability in gait speed is not accounted for in the statistical models reported to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Myriad influences, ranging from maintaining stability (Cooper et al, 2008) to sending signals about health and emotional state (Buchner et al, 1996;Schneider et al, 2014), will have some effect on the final optimization solution selected under a given circumstance. However, in most common situations, including the standardized circumstances of a laboratory investigation of walking or running, energetics will be a dominating contributor to the task faced by the individual, and thus will be a critical determiner of the effective optimization strategy.…”
Section: Abstract Locomotion Walking Task Constraint Economymentioning
confidence: 99%